A review of floating semisubmersible hull systems: Column stabilized unit. (1st November 2017) - Odijie, Agbomerie Charles; Wang, Facheng; Ye, Jianqiao
Abstract: Column stabilized semisubmersible is one of the most commonly used hull systems for the design and development of drilling and production platforms used for offshore deep water operations. Recent reconfiguration and design alterations have improved its hydrodynamic behaviour in rough weather conditions and, thus, its application and functionality in ocean engineering. Semisubmersible dry-trees applications and large wind turbine foundation systems in ultra-deep waters require high payload integration for reduced motion responses in all degrees of freedom. This paper presents a review of recent industrial and academic contributions to the development of column stabilized semisubmersible hulls used for deep water operations. It also provides an overview of the motion and structural attachments of semisubmersibles. The type and formation of dry-trees semisubmersibles are discussed. The dynamic behaviour and comparative advantages of them are also explained. Highlights: We systematically reviewed the development and application of semisubmersible structures in relation to oil and gas industry. We identified the gaps and promises to promote future research; and We created a comprehensive and informative resource for research students and researchers from both industrial and academic background.